2017
DOI: 10.1063/1.4983631
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear reconnecting edge localized modes in current-carrying plasmas

Abstract: Nonlinear edge localized modes in a tokamak are examined using global three-dimensional resistive magnetohydrodynamics simulations. Coherent current-carrying filament (ribbon-like) structures wrapped around the torus are nonlinearly formed due to nonaxisymmetric reconnecting current sheet instabilities, the so called peeling-like edge localized modes. These fast growing modes saturate by breaking axisymmetric current layers isolated near the plasma edge and go through repetitive relaxation cycles by expelling … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…4), as highly elongated layers cannot be stable against the plasmoid instability, also in 3D geometry (e.g. Daughton et al 2011;Sironi & Spitkovsky 2014;Guo et al 2015;Huang & Bhattacharjee 2016;Ebrahimi 2017;Baalrud et al 2018;Stanier et al 2019). Here, we show that plasmoids/flux ropes are self-consistently created in fully 3D plasma turbulence (see Sec.…”
Section: Plasma Turbulencementioning
confidence: 54%
“…4), as highly elongated layers cannot be stable against the plasmoid instability, also in 3D geometry (e.g. Daughton et al 2011;Sironi & Spitkovsky 2014;Guo et al 2015;Huang & Bhattacharjee 2016;Ebrahimi 2017;Baalrud et al 2018;Stanier et al 2019). Here, we show that plasmoids/flux ropes are self-consistently created in fully 3D plasma turbulence (see Sec.…”
Section: Plasma Turbulencementioning
confidence: 54%
“…The growth rate is calculated from the image data, and the results indicate that the mRT growth rate is in the order of 10 6 s −1 for PBEX. Another possible explanation is that a current-density layer forming at the bubble/background interface gives rise to growth of current-driven unstable filaments, 17 but further measurements would be needed to verify this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Additional interest in this stems from attempts to investigate the magnetohydrodynamic (MHD) instability of the plasma boundary for optimizing the energy confinement time for high fusion gain. 16,17 The experimental study of plasma motion across a transverse magnetic field has a long history. [18][19][20][21] Modern experimental investigations include those using pulsed-power-driven plasma guns, [22][23][24][25][26] radial wire array Z pinches, [27][28][29][30] and laser-produced plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations have demonstrated that filaments rotate toroidally because of the momentum injected into the plasma by energetic neutral beam injection heating systems and poloidally owing to diamagnetic and neoclassical effects 48 . Another feature that is well reproduced by MHD modelling is the current carried by filaments, which is typically of the level of the bootstrap current at the plasma edge before the ELM onset 50 . In addition, the number of filaments that erupt in a given ELM (equivalent to the toroidal mode number n) has been shown to be described well by simulations 51,52 .…”
Section: Box 1 | Equilibrium Pressure and Current Profiles And Tokammentioning
confidence: 93%